USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTs) AMONG WOMEN FARMERS IN NORTH-EASTERN NIGERIA (2011)
Availability of information on improved technologies is an important ingredient for agricultural development. However, Nigerian women farmers have low access to technological information. The use of Information and Communication Technologies (ICTs) among these women in accessing information on improved agricultural practices has not been adequately explored. Use of ICTs among women farmers in north-eastern Nigeria was assessed in this study. Adamawa and Bauchi were randomly selected from the six states in north-eastern Nigeria. All the seven Agricultural development Programme (ADP) zones in the two states were included in the sample. Twenty five percent of Women-in-Agriculture units of the ADP extension blocks in each zone were selected and 15% of women in each unit were randomly sampled. A total of 359 respondents, made up of 172 and 187 from Adamawa and Bauchi States respectively, were selected. Interview schedule was used to collect information on respondents‟ characteristics and benefits. Social participation, awareness and attitude were assessed and categorised on point scales thus: low (0-11.4), high (11.5-39.0); low (0-5.9), high (6.0-10); and unfavourable (37.0-60.0), favourable (61-79) respectively. The use of old ICTs (radio, television, telephone, video, extension bulletin and newspaper) and new ICTs (mobile phone, computer, internet and CD-ROM) were also assessed. Data were analysed, using descriptive statistics, Chi-square, correlation, t-test, and logit regression (p=0.05) Married respondents constituted 86.6% and the mean age was 41.0 ± 12.6 years. Christians were 65.1%, Muslims in seclusion were 32.9% and 52.0% attained primary education. Most respondents (64.3%) practised mixed farming, with mean farm size of 3.4 ± 2.7 ha; 93.0% cultivated cereals and 58.5% raised poultry. Also, 57.7% had low social participation score (0.0-11.4) and 99.0% were aware of ICTs. Majority of the respondents benefitted from access to information on fertiliser sources and application (75.8%), credits, grants and loans (71.5%), child care and nutrition (67.1%), market prices and location (65.5%), crop pests; diseases and control (63.5%). The most commonly used old ICTs were radio (92.8%) and television (59.6%), while the most commonly used new ICT was the mobile phone (59.3%). Fifty-two percent had unfavourable attitude (0.0-60.0) towards the use of ICTs. Use of ICTs was significantly related to residence location (χ2=0.12), seclusion status (0.44) and education (0.10). It was also significantly related to social participation (r=0.47), cosmopoliteness (0.19), awareness (0.65) and attitude (0.32). Mean awareness of old ICTs (4.1±1.9) was significantly higher than of new ICTs (1.7±1.3). Mean use of old ICTs (14.8±11.3), its use among non-secluded (21.5±6.8) and among urban respondents 4(23.1±16.6) were significantly higher than mean use of new ICTs (4.8 ±3.2), its use among secluded (15.7 ±9.3) and among rural respondents (19.2±12.4). Education, social participation, awareness of ICTs, cosmopoliteness and residence location had likelihood of increasing the use of ICTs by 0.03, 0.01, 0.46, 0.04 and 0.09 respectively Women farmers in north-eastern Nigeria had high awareness of ICTs and used them in accessing agricultural and other livelihood information. However, the unfavourable attitude and low awareness and use of new ICTs need to be addressed to increase the potential to deliver agricultural information to women farmers.